Phacogoniotomy versus phacotrabeculectomy for advanced primary angle-closure glaucoma with cataract: A randomized non-inferiority trial - Yunhe Song; Fengbin Lin; Aiguo Lv; Yao Zhang; Lan Lŭ; Lin Xie; Guangxian Tang; Huiping Yuan; Yangfan Yang; Jiangang Xu; Ping Lu; Meichun Xiao; et al. (2024)
To investigate the effectiveness and safety of phacogoniotomy versus phacotrabeculectomy (PVP) among patients with advanced primary angle-closure glaucoma (PACG) and cataracts. Multicenter, randomized controlled, non-inferiority trial. A total of 124 patients (124 eyes) with advanced PACG and cataracts were enrolled, with 65 in the phacogoniotomy group and 59 in the phacotrabeculectomy group. Patients were followed up for 12 months with standardized evaluations. The primary outcome was the reduction in intraocular pressure (IOP) from baseline to 12 months postoperatively, of which a non-inferiority margin of 4 mmHg was evaluated. Secondary outcomes included the cumulative surgical success rate, postoperative complications, and changes in the number of glaucoma medications. After 12 months, phacogoniotomy demonstrated non-inferiority to phacotrabeculectomy in terms of IOP reduction, with mean IOP reductions of − 26.1 mmHg and − 25.7 mmHg (P = 0.383), respectively, from baseline values of around 40 mmHg. Both groups experienced a significant reduction in the mean number of medications used postoperatively (P < 0.001). The cumulative success rate was comparable between the groups (P = 0.890). However, phacogoniotomy had a lower rate of postoperative complications and interventions (12.3% and 4.6%) compared to phacotrabeculectomy (23.7% and 20.3% respectively). The phacogoniotomy group reported shorter surgery time (22.1 ± 6.5 vs. 38.8 ± 11.1 min; P = 0.030) and higher quality of life (EQ-5D-5 L) improvement at 12 months (7.0 ± 11.5 vs. 3.0 ± 12.9, P = 0.010) than the phacotrabeculectomy group. Phacogoniotomy was non-inferior to phacotrabeculectomy in terms of IOP reduction for advanced PACG and cataracts. Additionally, phacogoniotomy provided a shorter surgical time, lower postoperative complication rate, fewer postoperative interventions, and better postoperative quality of life.